Frequency of mental distress among medical students from selected medical colleges of Pakistan: a systemic review - Syeda Rubaba Azim; Nooreen Adnan; Syeda Nazish Azim; Munizah Nisar; Muhammad Shahid Shamim (Journal of the Pakistan Medical Association, 2022)
Objective: To find out the frequency of mental distress among medical students in Pakistani medical colleges. Method: The systematic review comprised a search on PubMed and Google Scholar databases for articles published in English language between 2004 and 2019 having the key words ‘mental distress’, ‘medical undergraduate’, ‘depression’ and ‘anxiety’. After a four-phase scrutiny process, articles were shortlisted for detailed review. Conventional content analysis was utilised for data analysis. Results: Of the 30 articles, 18(60%) were reviewed in detail. Distress among Pakistani medical students was reported up to 90% which is alarmingly high. Study year, financial issues and academic burden were the noteworthy causal factors. Academics and examinations were substantial stress factors and religion was the commonly adopted coping strategy. Conclusions: Multiple studies showed evidence of an increasing rate of mental distress among medical undergraduates having various causative factors, mainly the academic burden. Key Words: Mental stress, Medical undergraduates, Pakistani medical college, Depression and anxiety stress.